RETRACTED: An Energy Based Approach to Determine the Plastic Limit of Fine-grained Soil Using Modified Cone Penetrometer. (2016) - Saxena, Mukul; Arora, V.K.
Abstract : This article has been retracted: please see Elsevier Policy on Article Withdrawal (http://www.elsevier.com/locate/withdrawalpolicy ). This article has been retracted at the request of scientific committee of RAEREST 2016. The authors have plagiarized part of a paper that had already appeared in Proceedings of the Institution of Civil Engineers - Geotechnical Engineering, 168 (2015) 53 - 64. DOI: 10.1680/geng.14.00004. One of the conditions of submission of a paper for publication is that authors declare explicitly that their work is original and has not appeared in a publication elsewhere. Re-use of any data should be appropriately cited. As such this article represents a severe abuse of the scientific publishing system. The scientific community takes a very strong view on this matter and apologies are offered to readers of the journal that this was not detected during the submission process.